Cirrus formation regimes – data-driven identification and quantification of mineral dust effect - K. Jeggle; D. Neubauer; H. Binder; U. Lohmann (Atmospheric Chemistry and Physics)
The microphysical and radiative properties of cirrus clouds are strongly dependent on the ice nucleation mechanism and origin of the ice crystals. Due to sparse temporal coverage of satellite data and limited observations of ice-nucleating particles (INPs) at cirrus levels, it is notoriously hard to determine the origin of the ice and the nucleation mechanism of cirrus clouds in satellite observations. In this work we combine 3 years of satellite observations of cirrus clouds from the DARDAR-Nice retrieval product with Lagrangian trajectories of reanalysis data of meteorological and aerosol variables calculated 12 h backward in time for each observed cirrus cloud. In a first step, we identify typical cirrus cloud formation regimes by clustering the Lagrangian trajectories and characterize observed microphysical properties for in situ and liquid origin cirrus clouds in mid-latitudes and the tropics. On average, in situ cirrus clouds have smaller ice water content (IWC) and lower ice crystal number concentration (Nice) and a strong negative temperature dependence of Nice, while liquid origin cirrus have a larger IWC, higher Nice and a strong positive temperature dependence of IWC. In a second step, we use MERRA2 reanalysis data to quantify the sensitivity of cirrus cloud microphysical properties to a change in the concentration of dust particles that may act as INPs. By identifying similar cirrus cloud formation pathways, we can condition on ice origin, region, and meteorological dependencies, and quantify the impact of dust particles for different formation regimes. We find that at cloud-top median Nice decreases with increasing dust concentrations for liquid origin cirrus. Specifically, the sensitivities are between 6 % and 7 % per order of magnitude increase in dust in the tropics and between 15 % in the mid-latitudes. The decrease in Nice can be explained by increased heterogeneous ice nucleation in the mixed-phase regime, leading to fewer cloud droplets freezing homogeneously once the cloud enters the cirrus temperatures and glaciates. The resulting fewer, but larger, ice crystals are more likely to sediment, leading to reduced IWC, as for example observed for liquid origin cirrus in the mid-latitudes. In contrast, for high-altitude in situ cirrus in the tropics, we find an increase of Nice median values of 11 % and IWC median values of 17 % per unit increase of dust aerosol in logarithmic space. We assume that this is caused by heterogeneous nucleation of ice initiated by dust INPs in INP-limited conditions with supersaturations between the heterogeneous and homogeneous freezing thresholds. Such conditions frequently occur at high altitudes, especially in tropical regions at temperatures below 200 K.